Makna Teologis dalam Tradisi Mangenta di Jemaat GKE Mandomai - Tahan Mentria Cambah; Retni Mulyani; Alexandra Binti (Unit Penerbitan Informasi dan Teknologi Sekolah Tinggi Teologi Gereja Kalimantan Evangelis (STT GKE), 2024)
The mangenta tradition is an agricultural tradition among the Ngaju Dayak tribe. This tradition is also practiced among the congregation members of the GKE Mandomai Church. Research on the mangenta tradition, as far as the team knows, has never explored its theological meaning. Therefore, the team researched and wrote about it. This research was conducted qualitatively. The initial investigation was done by examining writings related to local wisdom, the mangenta tradition and Mandomai. After that, the team was on location observing and interviewing various informants and phenomena related to the mangenta tradition. After that, the writing team formulated the theological meanings associated with these traditions. The team found that this tradition has begun to be uprooted among members of the GKE Mandomai congregation. Even though, the theological values contained therein are very valuable to maintain. The theological meanings found include togetherness or kapakat, unity or kahinje, expressions of gratitude/kahanjak, intimacy/kasene arep/tawan ekae and accuracy/pas, dia labih, dia kurang.